THE INFLUENCE OF IPS LEARNING RESULTS OF CLASS IV SD STUDENTS USING THE SNOWBALL THROWING MODEL - Lasari, Yufi Latmini (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Abstract :The problem in this study is the result of learning IPS students of grade IV SDN 03 Bandar Buat, Low Padang city. An alternative to solving the problem is to apply the Snowball Throwing model. This research aims to describe the design, implementation and learning outcomes of students of IPS class IV SD using the Snowball Throwing model. This type of research is classroom action research (CAR) with a qualitative and quantitative approach. The results of this study showed influence from the application of the Snowball Throwing model to the learning outcomes of IPS in grade IV students, namely on the average I cycle of learning outcomes of 60.7 students and increased in cycle II by an average of 85.7. Keywords: Learning Results, IPS, Snowball Throwing Model